Implementation of a Website for Booking Hajj Umrah and Tour Tickets Using the Waterfall Method - S Susliansyah; Heny Sumarno; Hendro Priyono; Linda Maulida (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
PT. Qonita Zikra Semesta fully needs an information system that supports and provides information and good service for customers. That is why the writer tries to make her Final Assignment concerning with the travel ticket reservations system with waterfall method, choosing this method because this method is ordered starting from the analysis, design, coding, testing, and support. Because at this time the existing system is still done manually, starting from customer registration to storing data related to the order process, to making reports. So that it is possible when the order process takes place arises problems such as recording errors during registration, loss of data, duplication of data, burning of documents, and late reporting because the data must be searched first and takes a long time. The design of this information system is the best solution to solve the problems that exist in this company. With a computerized system that can make a company work effectively and efficiently and in a booking system that is now much more conducive and well recorded than the system that is still manual as before